A general bearing deformation model for timber: Compression perpendicular to grain. (20th March 2018) - Leijten, A.J.M.
Highlights: Structural design models for bearing deformation of timber beams have not yet been accepted in the major building design codes over the world. A new and simple model for the bearing deformation is proposed and compared with three other models. The evaluation used a new data base of more than 1100 experimental test results covering softwood and hardwood species and most load cases that occur in building practice. The new model is the preferred model because of its reliability in accurate prediction and ease of use for the practical engineer. Abstract: This study focuses on a new and unique model to determine the elastic bearing deformation of structural timber. Available models that aim to predict the deformation are usually limited in their application. The performance of a simple model is compared to three other models, all being evaluated using experimental test data for the wood species Norway Spruce, Poplar, Beech, Cumaru and Akki and covering eight different load cases. The results show a simple model to have the best performance in deformation prediction and so is a potential candidate for introduction in updated structural timber design codes.